2 - Transcending the State–Market Dichotomy, Developmentalism and Industrial Change: Learning from Critical African Scholars - Ikpe, Eka (Africa Development, 2021)
Claude Ake presents the study of development as underpinned by Eurocentric teleologism. This refers particularly to how Western social sciences have been shaped around key disciplines that have been designed to restrain the ‘dynamic character of reality’, with a focus on analysing order as opposed to change. This article demonstrates the intellectual and practical limitations of linear understandings of change and transition that abstract from the ‘dynamic character of reality’ through disciplinary and other modes of confinement. This has, for instance, underpinned the tendency towards dichotomisation between the state and market across the ideological spectrum, in the study of development. The article responds to this challenge by centring critical African development thought in the work of Claude Ake, Thandika Mkandawire and Adebayo Olukoshi, and shows how conceptual development and analyses that are grounded in empirical experiences of transition problematise strict delineations of the milieus of the state and market, and the limiting of industrial development to particular sectors. In doing so, it showcases how progressing beyond linear analyses of transition, such as through paradigm extension of the developmental state paradigm to the enhanced developmental state paradigm, draws on the work of these key critical scholars.